Contact Dermatitis Associated With Hair Care Products: A Retrospective Analysis of the North American Contact Dermatitis Group Data, 2001–2016. Issue 1 (January 2022) - Warshaw, Erin M.; Ruggiero, Jenna L.; DeKoven, Joel G.; Maibach, Howard I.; Atwater, Amber R.; Taylor, James S.; Zug, Kathryn A.; Reeder, Margo J.; Silverberg, Jonathan I.; Sasseville, Denis; Fowler, Joseph F.; Fransway, Anthony F.; et al.
Abstract : Background: Hair care products (HCPs) may cause both allergic contact dermatitis (ACD) and irritant contact dermatitis (ICD). Objectives: The aims of the study were to determine the prevalence of HCP-associated ICD/ACD and to characterize relevant allergens. Methods: This study is a retrospective analysis of North American Contact Dermatitis Group (NACDG) patch test data, 2001–2016. Results: Of 38, 775 patients tested, 3481 (9.0%) had positive patch test reactions associated with HCPs. The HCP-positive patients were significantly more likely to be female (79.9% vs 66.0%) and/or have primary sites of dermatitis on the face (32.0% vs 27.8%) or scalp (15.4% vs 2.2%) compared with the HCP-negative patients ( P < 0.0001). Of 4908 HCP-associated positive patch test reactions, 86.9% (n = 4263) were due to allergens on the NACDG screening series; p -phenylenediamine (35.8%), methylisothiazolinone (9.7%), methylchloroisothiazolinone/methylisothiazolinone (8.7%), and cocamidopropyl betaine (5.9%) were the most frequent. Most reactions (87.7%, 3736/4263) were currently clinically relevant. The most common job associated with 366 occupationally related NACDG HCP-associated allergens was hairdresser/cosmetologist (71.9%). Two hundred eighty-two patients (0.7%) had ICD associated with HCPs. Shampoo/conditioners were the most frequent source of NACDG HCP-associated reactions (47.3%) and HCP-associated ICD (45.0%). Conclusions: Of the HCP-positive patients, 18.5% had HCP reactions to allergens not on the NACDG screening series, underscoring the importance of patch testing to expanded series in patients suspected of HCP allergy.